Genre based navigation on the Web - Roussinov, Dmitri; Kevin Crowston; Nilan, Michael; Kwaśnik, Barbara H.; Xiaozhong Liu; Cai, J. (Proceedings of the 34th Hawai'i International Conference on Systems Science (HICSS), 2001)
We report on our ongoing study of using the genre of Web pages to facilitate information exploration. By genre, we mean socially recognized regularities of form and purpose in documents (e.g., a letter, a memo, a research paper). Our study had three phases. First, through a user study, we identified genres which most/least frequently meet searchers' information needs. We found that certain genres are better suited for certain types of needs. We identified five (5) major groups of document genres that might be used in an interactive search tool that would allow genrebased navigation. We tried to balance the following dual objectives: 1) each group should be recognizable by a computer algorithm as easily as possible 2) each group has a better chance of satisfying particular types of information needs. Finally, we developed a novel user interface for a web searching that allows genre-based navigation through three major functionalities: 1) limiting search to specified genres 2) visualizing the hierarchy of genres discovered in the search results and 3) accepting user feedback on the relevancy of the specified genres.